How the Perception of Corruption Shapes the Willingness to Bribe: Evidence From An Online Experiment - (:unkn) unknown (Oxford University Press, 2024)
Does the perception of corruption shape the willingness to bribe? This study evaluates the socio-psychological determinants of corruption by measuring how different types of messages influence the probability of engaging in corruption for access to publi...
Keywords: Corrupción; Soborno